REVIEW. - Andreea-Diana SCODA (National Centre for Policy and Evaluation in Education, 2018)
REVIEW. ALETHA JAUCH SOLTER. JOCUL ATAŞAMENTULUI. REZOLVAREA PROBLEMELOR DE COMPORTAMENT ALE COPILULUI PRIN JOACĂ, RÂS ŞI CONECTARE. (Attachment Play: How To Solve Children's Behaviour Problems With Play, Laughter, And Connection. Shining Star Press, 2013) Bucharest, Herald Publishing House, 2015, 272 pages, ISBN 978-973-111-624-2